Praktik Jual Beli Emas Anggota Majelis Ta'lim Al-Hijrah Gunung Binjai Balikpapan - Marhamah Masykur; Adara Elthani Safrina; Rukmana Rukmana (LPPM STIS Hidayatullah, 2022)
Islam groups gold and silver as usury objects. Consequently, the exchange (buying and selling) of such objects must pay attention to the provisions that have been outlined by Shari'a so as not to fall into the practice of usury. Therefore, there are special rules in the gold and silver business. The purpose of this study is to find out the practice of buying and selling gold for members of Majelis Ta'lim Al-Hijrah of Gunung Binjai, and also to find out how the practice is from the perspective of Islamic law. This type of research is a field research that uses a descriptive qualitative analysis pattern through a phenomenological approach. The researcher chose to use this approach because through this approach the researcher tried to bring out reality naturally through provocation questions, then the research subject was left to describe all kinds of dimensions of his experience based on the phenomena that occurred. The results of this study are that there are two methods used by members of MT al-Hijrah to trade the gold. First, the cash method (cash) at the gold shop. Second, the arisan method. The two methods used are in accordance with the Shari'ah, because they meet the legal requirements of the gold trade contract. There are two purposes of the gold transaction, namely as savings (investment) and used for jewelry.